EFEKTIVITAS BERKUMUR DENGAN LARUTAN INFUSUM KISMIS (VITIS VINIFERA L) TERHADAP PENURUNAN INDEKS PLAK GIGI - Elyasina Elyasina; Rizanda Machmud; Murniwati Murniwati (Andalas Dental Journal, 2015)
Plaque is the main factor in progress periodontal disease and dental caries. Plaque control is elimination and inhibit of dental plaque accumulation at tooth surface. Plaque control can be done mechanically and chemically. In this study, used a solution of raisin infusion (Vitis vinifera L) as a mouthwash, because there are various phytochemical capable of inhibiting plaque formation. The aim of this study was to know the effect of raisin infusion solution on decrease dental plaque index. This study is an experimental study with pretest and posttest control group design. The sample of this study was 56 students were divided randomly into four groups, which is one control group and three test groups. The test groups was given 20%, 40% and 60% of raisin infusion solution. Dental plaque score was measured with PHP Plaque Index. Statistical analisys was performed according to Anova one way with p<0,05. The result of this study is significant differences of dental plaque index of control group when compared to the test group with 40% solution of raisin infusion (p=0,004) and when compared to the test group with 60% solution of raisin infusion (p=0,000). Rinsing with the 40% and 60% solution of raisin infusion can reduction of dental plaque index.